2019
DOI: 10.1111/ppa.13064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and virulence of Xanthomonas campestris pv. campestris isolates from Brassica napus and six Brassica oleracea crops in Serbia

Abstract: The present study provides insight into the diversity of 147 Xanthomonas campestris pv. campestris (Xcc) isolates obtained from six Brassica oleracea vegetable crops (broccoli, cabbage, cauliflower, collard greens, kale, kohlrabi) and the winter oilseed rape crop Brassica napus, collected from different regions in Serbia in 2014. The XCF/XCR pathovar‐specific primer set was used for fast preliminary identification. In repetitive sequence‐based PCR (BOX, ERIC and REP) of all isolates, a higher level of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…A recent MLST-based study performed with the same four genes (P-X-dnaK, fyuA, gyrB, and rpoD) revealed the presence of as many as five (ST3, ST5, ST9, ST26, and ST47) different STs in the collection of fifteen Serbian Xcc strains obtained from winter oilseed rape (Brassica napus) over a nine-year period (2010-2018) (Jelušić et al, 2020). In another study on Xcc strains from Serbia, performed by Popović et al (2019), which was based on the phylogenetic analysis of ten housekeeping genes (dnaK, fusA, fyuA, rpoD, gapA, gyrB1, gyrB2, gltA, lacF, and lepA), it was noticed that strains that originated from broccoli, cauliflower, collard greens, kohlrabi and kale, along with cabbage, were genetically homogenous. The absence of genetic diversity among the strains obtained in 2014 indicates that the long tradition of brassica crops cultivation in Serbia has not caused an evolution of different Xcc populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent MLST-based study performed with the same four genes (P-X-dnaK, fyuA, gyrB, and rpoD) revealed the presence of as many as five (ST3, ST5, ST9, ST26, and ST47) different STs in the collection of fifteen Serbian Xcc strains obtained from winter oilseed rape (Brassica napus) over a nine-year period (2010-2018) (Jelušić et al, 2020). In another study on Xcc strains from Serbia, performed by Popović et al (2019), which was based on the phylogenetic analysis of ten housekeeping genes (dnaK, fusA, fyuA, rpoD, gapA, gyrB1, gyrB2, gltA, lacF, and lepA), it was noticed that strains that originated from broccoli, cauliflower, collard greens, kohlrabi and kale, along with cabbage, were genetically homogenous. The absence of genetic diversity among the strains obtained in 2014 indicates that the long tradition of brassica crops cultivation in Serbia has not caused an evolution of different Xcc populations.…”
Section: Resultsmentioning
confidence: 99%
“…Three representative Xcc cabbage strains isolated in Serbia in 2014, coded as Xc40, Xc48, and Xc75, were selected for allelic profile determination out of a total of 44 strains previously characterized by Popović et al (2019). The three strains were representative considering the high homology among Xcc populations from cabbage determined by the MLSA with ten housekeeping genes.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…campestris (Xcc) is ubiquitous worldwide as an agent causing disease of many Brassica crops, thereby being important economically (Ignatov et al, 2000;Vicente et al, 2001;Lema et al, 2011). Before its appearance on winter oilseed rape in Serbia, Xcc was described as a causal agent of black rot of different varieties of B. oleracea vegetable crops, including capitata (cabbage), botrytis (cauliflower), italica (broccoli), sabauda (kale), gongylodes (kohlrabi), and acephala (collard greens; Popović et al, 2019). Reports indicating appearance of Xcc on oilseed rape worldwide are scarce and are mostly only first reports, which were not followed by more detailed research, or where Xcc was used in host specificity studies.…”
mentioning
confidence: 99%
“…The first appearance of Xcc on winter oilseed rape in Serbia was reported on escaped plants of the domestic cultivar Slavica (Institute of Field and Vegetable Crops -IFVC, Novi Sad) in the Bačka region (Vojvodina, Serbia) in September 2010 (Popović et al, 2013(Popović et al, , 2014. Thereafter, since 2014, the disease has been appearing every year on cultivated winter oilseed rape crops (Popović et al, 2019) with symptoms of yellow to dark-brown, V-shaped necrotic lesions, starting from the leaf margins and progressing along the leaf veins. Popović et al (2019) called attention to the genetic heterogeneity of winter oilseed rape isolates, in contrast to the lack of genetic diversity among isolates from other studied B. oleracea hosts (broccoli, cabbage, cauliflower, kale, kohlrabi, and collard greens).…”
mentioning
confidence: 99%